Reliability and validity of the Turkish version of short form 36 (SF-36) in patients with rheumatoid arthritis - Bilir Kaya, Başak; İçağasıoğlu, Afitap (Journal of Surgery and Medicine, 2018)
Aim: Investigating reliability and validity of the Turkish version of short form-36 (SF-36) in patients with rheumatoid arthritis Methods: Demographic data of the patients with rheumatoid arthritis were recorded. Health Assessment Questionnaire (HAQ) and Short Form 36 (SF-36) were filled out. Disease activities were computed using Disease Activity Score 28 (DAS-28). Patients were recalled after three months and were asked to state how they felt compared to their first visit, and the same tests were repeated. Results: 141 patients were admitted (9.9% male, 90.1% female). In the reliability study of SF-36, the Cronbach alpha value of the subscales varied in the range 0.792-0.992, hence SF-36 was found to be highly reliable. The item total score correlations were computed for each subscale and were found to be in the ranges: 0.436-0.840 for physical functioning, 0.887-0.895 for role function (physical), 0.861-0.958 for pain, 0.564-0.892 for general health perception, 0.702-0.841 for vitality (energy/fatigue), 0.949-0.952 for social functioning, 0.396-0.473 for role function (emotional) and 0.456-0.824 for mental health. The SF-36 scores from two consecutive visits spaced 3 months apart were compared and the p values were found to be greater than 0.05. The validity study was conducted for the 63 patients whose reported conditions did not change between two visits. The test-retest relation was evaluated using intra-class correlation coefficients, which ranged from 0.51 to 0.78 and the correlations of the two tests were found to be statistically significant. The comparison of SF-36 scores from two consecutive visits, all with p>0.05, showed no statistically significant changes. Conclusions: The Turkish version of SF-36 was found to be reliable and valid in patients with rheumatoid arthritis.